Feasibility Analysis of the Bonto River, Tomon 1 Village, Dekai District, Yahukimo Regency as a Source of Raw Water - T. Bernathius Julison; Mujiati Mujiati; Amaliah Azis; Firman Setiawan; Anastasya Coria Ayomi (Publikasi Indonesia, 2024)
Rivers are one of the sources of water for the life of living things. Rivers are often used in various ways by humans. The Bonto River is one of the rivers in Yahukimo Regency that is used as raw water for drinking water. In order to meet the need for clean water, it is necessary to analyze the water quality of the Bonto River. Determining the source of raw water in an area is the first step in determining the location or place as a raw water supplier for clean water treatment purposes. The purpose of this study is to identify the water quality of the Bonto river and evaluate the condition of the Bonto river water with the water quality standards that have been set to be used as an alternative source of raw water for clean water treatment. Water sampling in this study was carried out by observation and measurement directly in the field, and laboratory tests. Raw water quality data is compared to the current raw water and drinking water quality standards. The water quality standards used are the Decree of the Minister of Health of the Republic of Indonesia Number: 492/MENKES/SK/IV/2010, dated April 19, 2010 concerning the Terms and Conditions and Supervision of Drinking Water Quality, and in accordance with the water quality requirements. Each sample of water and sediment is examined in the laboratory to be analyzed according to its needs, namely regarding water quality. Testing of water quality samples was carried out at the Papua Regional Health Laboratory Center.